Comparison between OCT and Fundus photography on cup-to-disc ratio and Arteriolar-to-Venular ratio measurements - Othman, Shah Farez; Ho, Kang Guan (IIUM, 2021)
Different clinical equipment may use different methods to assess cup-to-disc ratio (CDR) and arteriolar-to-venular diameter ratio (AVR) that may result in different readings. This study was conducted to compare the CDR and AVR measurements between optical coherence tomography (OCT) and fundus photography (FP). Thirty-four (34) subjects were recruited into this clinical cross-sectional study. The mean aged of subjects was 22.90 ± 1.33 years, ranging from 21 to 27 years. Whereas the mean spherical equivalent refraction was -3.04 ± 2.42 D, ranging from +0.25 to -9.25 D. For the OCT, a 3D Optic Disc Scan protocol was used to measure CDR and AVR. Whereas a planimetry technique was used to obtain CDR and AVR measurements from the FP image output. The mean CDR and AVR obtained from OCT were 0.51 ± 0.08 and 0.74 ± 0.06, respectively. Whereas, the mean CDR and AVR obtained from FP were 0.41± 0.05 and 0.64 ± 0.05, respectively. There were statistical significant differences in the mean CDR and AVR between OCT [t(33) = 7.21, p<0.01] and FP [t(33) = 11.25, p<0.01] measurements. The CDR and AVR from OCT measurement were higher compared to the FP. In conclusion, during a routine clinical measurement for CDR and AVR, the various clinical equipment used must be taken into consideration before making a clinical diagnosis.